Thyroid hormone and the developing hypothalamus - Alkemade, Anneke (Frontiers in Neuroanatomy, 2015)
Thyroid hormone (TH) plays an essential role in normal brain development and function. Both TH excess and insufficiency during development lead to structural brain abnormalities. Proper TH signaling is dependent on active transport of the prohormone thyroxine (T4) across the blood-brain-barrier and into brain cells. In the brain T4 undergoes local deiodination into the more active 3,3′,5-triiodothyronine (T3), which binds to nuclear TH receptors (TRs). TRs are already expressed during the first trimester of pregnancy, even before the fetal thyroid becomes functional. Throughout pregnancy, the fetus is largely dependent on the maternal TH supply. Recent studies in mice have shown that normal hypothalamic development requires intact TH signaling. In addition, the development of the human lateral hypothalamic zone coincides with a strong increase in T3 and TR mRNA concentrations in the brain. During this time the fetal hypothalamus already shows evidence for TH signaling. Expression of components crucial for central TH signaling show a specific developmental timing in the human hypothalamus. A coordinated expression of deiodinases in combination with TH transporters suggests that TH concentrations are regulated to prevent untimely maturation of brain cells. Even though the fetus depends on the maternal TH supply, there is evidence suggesting a role for the fetal hypothalamus in the regulation of TH serum concentrations. A decrease in expression of proteins involved in TH signaling towards the end of pregnancy may indicate a lower fetal TH demand. This may be relevant for the thyrotropin (TSH) surge that is usually observed after birth, and supports a role for the hypothalamus in the regulation of TH concentrations during the fetal period anticipating birth.